2017
DOI: 10.1051/epjconf/201714302091
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer in a confined impinging jet with swirling velocity component

Abstract: Abstract. Heat transfer measurements based on an infrared experimental method (TOIRT) are compared with CFD simulations of a confined impinging jet with tangential velocity component. The tangential velocity component added to a pure impinging jet introduces into the flow field and heat transfer some similarities with real industrial processes like agitated vessels with axial-flow impellers. The tangential velocity component significantly influences the velocity field and heat transfer intensity in the stagnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Memar, et al [13] studied convective heat transfer data from a confining tube to coaxial, counter-swirled jets and observed that peak Nusselt number was shifted upstream with the increase of inner jet swirl strength. Petera, et al [14] studied both experimentally and numerically heat transfer measurements of a confined impinging jet with a tangential velocity component. They found that the addition of the tangential velocity component significantly influences the velocity field and the intensity of heat transfer in the stagnant region compared to the classical characteristics of the impinging jet.…”
Section: Introductionmentioning
confidence: 99%
“…Memar, et al [13] studied convective heat transfer data from a confining tube to coaxial, counter-swirled jets and observed that peak Nusselt number was shifted upstream with the increase of inner jet swirl strength. Petera, et al [14] studied both experimentally and numerically heat transfer measurements of a confined impinging jet with a tangential velocity component. They found that the addition of the tangential velocity component significantly influences the velocity field and the intensity of heat transfer in the stagnant region compared to the classical characteristics of the impinging jet.…”
Section: Introductionmentioning
confidence: 99%